Pengaruh Variasi Konsentrasi Chitosan Sebagai Bahan Penghancur Terhadap Sifat Fisik Sediaan Orally Disintegrating Tablet (ODT) Paracetamol - Kristin Sulistriyani; Desy Nawangsari; Khamdiyah Indah Kurniasih (Poltekkes Kemenkes Padang, 2022)
An antipyretic analgesic drug called paracetamol is used in children to treat mild to moderate pain and fever. Orally Disintegrating Tablet (ODT), a medicine that dissolves in seconds, was created to help children who have difficulty swallowing tablets. The purpose of this study was to determine the effect of changes in the concentration of chitosan as a disintegrant in the formulation of ODT paracetamol. These ODT tablets are made using a wet granulation process. Paracetamol ODT tablets were produced in three formulations with 3.5% chitosan concentration; 7% and 14%. The findings showed that the optimal concentration of chitosan was 3.5%, which had an impact on the physical characteristics and dissolution of tablets. The results showed that paracetamol F1 ODT preparation with 3.5% chitosan concentration was the best formula. This was caused by chitosan with an average weight uniformity test value of 202.65±2.00 mg; uniformity of diameter and thickness 0.831±0.008 cm and 0.343±0.008 cm, hardness 5.4±0.34 kg; brittleness 0.23±0.02; disintegration time 24 seconds; da dissolution 99.56%. The findings for hardness (p= 0.011), friability (p= 0.046), and disintegration time (p= 0.000) all showed significant variation (p 0.05). It was concluded that the disintegration time of the tablets increased with the increase in the chitosan content. It is recommended that further research be conducted for analgesic and antipyretic tests to determine whether the tablets have an effective analgesic and antipyretic effect.